The Impact of Leverage, Managerial Ownership, and Capital Intensity on Tax Avoidance - Nailufaroh, Lulu; Suprihatin, Neneng Sri; Mahardini, Nikke Yusnita (Jurnal Keuangan dan Perbankan (KEBAN), 2022)
The purpose of this study is to examine the effect of Leverage, managerialownership and capital intensity on tax avoidance in real estate companies listedon the Indonesia Stock Exchange for in 2017-2019. Determination of samplesusing purposive sampling method and obtaining 23 companies with certaincriteria. The analysis technique used in this study is multiple linear regression.The results showed that the leverage and capital intensity have no significanteffect on tax avoidance. While management ownership has a significant effect ontax avoidance